AN ATTITUDINAL SYSTEM ANALYSIS OF TEACHER’S TALK IN EFL CLASSROOM INTERACTION - Evi Septiani Rahayu; Rama Dwika Herdiawan; Eva Fitriani Syarifah (ETERNAL (English Teaching Journal), 2020)
This present study is intended to analyze the dominant type of attitudinal system that expressed by the teacher. This study utilized qualitative method with Critical Discourse Analysis (CDA) as research design. As for research sampling, this study involved an English teacher and one science class of eleventh grade students in one of secondary school in Majalengka. In order to collect the data, the researcher utilized the instrument of observation. Then, this data were analyzed by using Appraisal Theory that proposed by Martin and Rose (2007). As for the results, this research found that the dominant type of attitudinal system that expressed by the teacher is Affect category. It indicated that both the teacher frequently expressed his opinion, feeling and emotion through their talk. Furthermore, these talks mostly expressed in positive way. It indicated that the teacher always tried to build a positive atmosphere by saying positive talks in order to stimulate the students to become active in the classroom. Therefore, it can be said that it is very important for the teachers to pay more attention in managing their talk since it can affect students’ interaction in the classroom.